Hubungan Antara Parenting Stress Dengan Strategi Regulasi Emosi Orang Tua yang Memiliki Anak Usia Sekolah Dasar (Middle Childhood) di JABODETABEK - Lutfi, Srifianti (Jurnal Psikologi : Media Ilmiah Psikologi, 2020)
AbstractThe increasing number of violence against children, which in 2015 was reported to be 1,975 increased to 6,820 cases in 2016. This shows that the psychological condition of parents can influence how their behavior is in care and greatly influences the child's development. Parents who have children who are at a critical stage of development that is the age of elementary school (Middle Childhood) where at this age is the first experience of school in children and various demands for development tasks and school work begins. This will be a stressor for parents. If parents can not regulate the emotions they feel it will be associated with higher levels of parenting stress. The purpose of this study is to analyze how the relationship between parenting stress and emotional regulation strategies of parents who have elementary school age children in Jabodetabek. The population and sample in this study are parents who have Elementary School Age Children (Middle Childhood), amounting to 241 people. The measuring instrument used to measure Parenting Stress is a measuring tool developed by Berry and Jones (1995) with a total of 18 items and after being tested into 16 items with a reliability value of 0.87. While the measuring tool to measure the Emotion Regulation was developed by Gross and John (2003) with 10 items. And after testing the reliability value of 0.75 obtained for aspects of cognitive reappraisal. As for the Expressive Suppression aspect, it has a reliability value of 0.71. The research method used is a quantitative descriptive study with correlational methods, and the analytical test used is to use correlation analysis from Charles Spearman. The statistical test results obtained -0.200 with a significance level of 0.01 which means there is a negative relationship between parenting stress with emotional regulation strategies of parents who have elementary school age children (Middle Childhood) in JABODETABEK. Keywords: Parenting Stress, emotion regulation, middle childhood  AbstrakMeningkatnya angka kekerasan pada anak, yang pada tahun 2015 dilaporkan berjumlah 1.975 meningkat menjadi 6,820 kasus di tahun 2016. Hal ini menunjukkan kondisi psikologis orang tua dapat memengaruhi bagaimana perilakunya dalam pengasuhan dan sangat memengaruhi perkembangan anak. Orangtua yang memiliki anak yang berada pada tahapan perkembangan yang kritis yakni usia Sekolah Dasar (Middle Childhood) dimana pada usia ini merupakan pengalaman pertama sekolah pada anak dan berbagai tuntutan tugas perkembangan dan tugas sekolah dimulai.  Hal ini akan menjadi stressor bagi orang tua. Apabila orang tua tidak dapat mengatur emosi yang dirasakannya maka akan berkaitan dengan tingkat stres orang tua yang lebih tinggi. Tujuan dari penelitian ini yaitu menganalisis bagaimana hubungan  parenting  stress   dengan strategi regulasi emosi orang tua yang memiliki anak usia Sekolah Dasar (Middle Childhood) di kawasan JABODETABEK. Populasi dan sampel dalam penelitian ini adalah orang tua yang memiliki anak Usia Sekolah Dasar (Middle Childhood) yang berjumlah 241 orang. Alat ukur yang digunakan untuk mengukur Parenting Stress adalah alat ukur yang dikembangkan oleh Berry dan Jones (1995) dengan jumlah aitem adalah 18 aitem dan setelah diuji coba menjadi 16 item dengan nilai reliabilitas sebesar 0.87. Sedangkan alat ukur untuk mengukur Regulasi Emosi dikembangkan oleh Gross dan John (2003) dengan jumlah aitem sebanyak 10 aitem. Dan setelah diuji coba didapatkan  nilai reliabilitas sebesar 0,75 untuk aspek Cognitive Reappraissal. Sedangkan untuk aspek Expressive Suppression memiliki nilai reliabilitas 0,71. Metode penelitian yang dilakukan adalah studi deskriptif kuantitatif dengan metode korelasional, dan uji analisis yang digunakan adalah dengan menggunakan analisis korelasi dari Charles Spearman. Hasil uji statistik diperoleh hasil sebesar -0.200 dengan taraf signifikansi sebesar 0,01 yang berarti terdapat hubungan negatif antara parenting stress dengan strategi regulasi emosi orang tua yang memiliki anak usia Sekolah Dasar (Middle Childhood) di JABODETABEK. Kata kunci : Parenting Stress, regulasi emosi, middle childhood